Odpowiedzi

2009-11-14T18:58:31+01:00
Zad. 2
a)
a + b + c = 2 - 1 + ¼ = 1 + ¼= 1¼
b)
a(8c-b) = 2(8*¼+1) = 2 (2+1) 2 * 3 = 6
c)
2(a+b)(a-b)c = 2(2-1)(2+1)+¼=(4-2)(2+1)+¼=8+4-4-2=6
d)
¼(ab+bc+ac)=¼(2*(-1)+(-1)*¼+2*¼)=¼(-2-¼+½)=¼*(-1¾)=-⁷/₁₆
e)
4 *¼ - 1 + 10 * 2 + 15 = 1 - 1 + 20 + 15 = 35
-------------------------- -------------------- --------- = 7 (

(wszędzie pod kreską ułamkową ma być 5)

f)

2(a²+b²-4c)+3(a+2b-8c) = 2(4 + 1 -1 ) + 3( 2 - 2 - 2 ) = 2 * 4 + 3 * -2 = 8 - 6 = 2

2009-11-14T19:26:07+01:00
2
a) a+b+c = 2 + (-1) + ¼ = 1¼
b)a(8c-b) = 8ab - ac = 8*2*¼ - 2*¼ = 4 - ½ = 3,5
c)2(a+b)(a-b)c = 2a + 2b*ac - bc = 2a + 2abc - bc = 2*2 + 2*2*(-1)*¼ = 4*(-1)*¼ = -4*¼ = 1
d)¼(ab + bc + ac) = ¼ab + ¼bc + ¼ac = ¼*2*(-1) + ¼*(-1)*¼ + ¼*2*¼ = -½ -⅛ + ⅛ = -½
e)
4 *¼ - 1 + 10 * 2 + 15
-------------------------- =
5

1 - 1 + 20 + 15
----------------- =
5

35
--- = 7
5

f) 2(a²+b²-4c)+3(a+2b-8c) = 2a² + 2b²-8c + 3

postaram sie dzis zrobic reszte zadan ;)